南来书家崔大地： 身世、迁徙槟城及其槟城公共场所书法文物遗产*: The Chinese Calligrapher to the South: The Life Experiences of Tsue Ta Tee, Migration Journey to Penang and his Chinese Heritage Calligraphy Artwork in Penang’s Public Places - Seng, Tan Gian; Chee, Lee Soo (ERUDITE: Journal of Chinese Studies and Education, 2021)
二十世纪初期至中期的中国，时局变革，动乱忧患，天灾人祸频繁，是以中国士林书法艺术家播迁南来槟城避难，安身立命，传播知识等络绎不绝。他们于槟城所开展的文化教育及书艺的传播与影响迄今依然深刻，成为了槟城（华社）宝贵重要的文教资源与文献遗产。循此，本论文以文献分析，辅以访谈口述，著意勾勒中国南来的马新第一代著名书法名家崔大地（1903-1974）的身世：即其工作身份、名字、中国大陆时期的经历，并考察迁徙槟城的路径与旅居槟城时期的交游事迹。追溯其身世虽难有整全图象，然推进身世研究亦冀后来者继续补缀缺漏。此外，亦尝试探究其槟城公共场所的街招匾额书法文物之主要个别书体外，勾勒其个别书体且又能融汇了碑、隶、楷等多体的书写特点，从中指出它们及其书写特点之于槟城珍贵文物遗产和马来西亚书法艺术史之书写承先启后的意义。In early and mid-twentieth century, the changes of political situations, turmoil, hardships and natural disasters in China forced mass migration of Chinese hailed from China to Penang. Many of the migrants from China took refuge in Penang. Dedicated to their own origins of Chinese culture, education and art, they preserved the original sources of Chinese heritage and left behind their invaluable treasures which in one way or another shaped and formed the culture of Penang Chinese community today. Among those Chinese migrants to Penang, some of them were scholars, calligraphers and artists originally from China. Tsue Ta Tee, a prominent Chinese Calligrapher, found his feet and settled down in Penang from 1903 to 1974. This research is an attempt to explore his life experiences (e.g., job, name experiences in mainland China), migration journey to Penang, and social interactions in Penang. All these are the fundamental aspects which lay the foundation of the future research to further account for his past life experiences. Besides, this article also highlights Tsue Ta Tee’s Chinese calligraphy writing characteristics and styles based on the bills, tablets, and artwork through his seal inscription, official script and regular script which are displayed at numerous public areas located in Penang.  Through this research, it also mentions the important features of Tsue Ta Tee’s Chinese calligraphy and how his artwork is meaningful and has become one of the most precious cultural heritage treasures in Penang. Finally, his calligraphy artwork has played an important role in contribution to the history of Malaysian Chinese, particularly it helps establish the connection between the past and the future development of Chinese calligraphy in Malaysia. Keywords：Tsue Ta Tee，Chinese calligrapher to the south, life experiences, migration journey to Penang, Chinese calligraphy works in Penang’s public places, the heritage meanings